Separation Axioms via $F$-open Sets (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce some types of separation axioms via $F$-open sets, namely $FT_i$ ($i = 0, 1, 2, 3, 4$), $F$-regular and $F$-normal spaces, and investigate their properties, relationships and characterizations. We show that every $FT_i$ space is a Ti space for $i = 0, 1, 2, 3, 4$. However, the converse is true whenever X is finite.
Keywords: $F$-open, $FT_i$ ($i = 0, 1, 2, 3, 4$), $F$-regular, $F$-normal